Development of integrated framework for fatigue life prediction in welded structures. (July 2018) - Shiraiwa, Takayuki; Briffod, Fabien; Enoki, Manabu
Highlights: An extensible framework for fatigue life prediction in welded joint is proposed. The microstructure and residual stress is calculated by thermo-mechanical analysis. The stress field analysis is performed by importing the microstructure. The crack initiation life is evaluated by crystal plasticity model. The scattering of the fatigue life increases with decreasing the stress level. Abstract: A new fatigue prediction method for wide range of welded structures has been developed by integrating several advanced computational techniques such as thermo-mechanical finite element method, crystal plasticity model and extended finite element method. The method consists of the following procedures: (i) computation of materials properties; (ii) analysis of temperature field, microstructure and residual stress generated during a welding process; (iii) stress distribution analysis under cyclic loading; (iv) fatigue crack initiation analysis by the Tanaka-Mura model; (v) fatigue crack propagation analysis. Using the proposed methodology, the fatigue life of butt joint was evaluated and compared with the experimental data.